Konstruksi Makna dan Simbol Kecantikan Pada Tayangan Final Miss Universe 2019 - Rety Palupi; Andi Setyawan (LPPM UBSI, 2021)
Reality is essentially a social construction created by humans. Miss Universe is the biggest and oldest beauty contest platform in the world that reconstructs beauty in it. This study seeks to analyze the social construction of the meaning and symbol of beauty in the Miss Universe 2019 final show. The research approach is qualitative by collecting data in the form of documentation of the Miss Universe 2019 final show and the official website of Miss Universe. The data obtained were analyzed by semiotics using the Charles Sanders Peirce approach. The results obtained show that the construction of a beautiful woman to be slim, tall, white, and with long hair is not always proven. This is evidenced by the victory of Zozibini Tunzi from South Africa at Miss Universe 2019. The 2019 Miss Universe final proves that beautiful women are not always seen from the physical construction of society, but the advocacy they do is also a determinant of what she deserves to be called a universally beautiful woman.